OPTIMALISASI KANDUNGAN ASAP CAIR DARI TEMPURUNG KELAPA DAN SABUT KELAPA MELALUI PROSES PIROLISIS - Purnawati, Eka; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Coconut shell and husk was the waste wich has not been utilize optimally. They have a fairly high content of cellulose. The solution of this problem to become liquid smoke. The aim of this research was to detect the best yield result of liquid smoke that containet phenol and acid. Liquid smoke obtained from the condensation of fumes on pyrolysis of constituents such as cellulose, hemicellulose and lignin. Pyrolysis occurred for 5 hours at temperature of 400 Â° C. Two dominant resulting compound is phenol and organic acids which inhibit the growth of bacteria. The best results are found in liquid smoke grade 1 with grade phenol compound at 4.08%, 10.39% acidity and pH value of 1.4. The yield best results from the coconut husk is 32.6%. Key Word : Liquid Smoke, Pyrolysis, Phenol